Comportamiento productivo de gallinas de postura con dietas que contienen dos fuentes de Fitasa de Escherichia Coli - Bocanegra Valles, Lena Soledad (2013)
The present study aimed to evaluate the productive performance of laying hens to diets containing two sources of phytase from Escherichia coli. We used 168 commercial laying hens genetic line Hy Line Brown of 43-55 weeks of age on three treatments: (T0), (T1) and (T2) using completely randomized design. Each treatment consisted of 8 repetitions with 7 birds each, reared under the same conditions of handling, feeding and health. We evaluated the percentage of production, number of eggs per hen housed, kilogram per hen housed egg, percentage of broken eggs, white and dirty, feed conversion, weight gain. Statistically significant difference was found among treatments for egg laying rate (P <.05). While numerical difference was the number of eggs per hen housed, kilogram of eggs per hen housed, percentage of broken eggs, white and dirty, feed conversion, weight gain, these were not statistically significant (P> .05). There were no problems of morbidity, mortality. We conclude that the addition of phytase source B Escherichia unlike Escherichia coli phytase A source significantly increases the percentage of posture (P <0.05) during the 43 and 55 weeks of age.